Potential of Dried Blood Self-Sampling for Cyclosporine C2 Monitoring in Transplant Outpatients. (20th May 2010) - Leichtle, Alexander Benedikt; Ceglarek, Uta; Witzigmann, Helmut; Gäbel, Gábor; Thiery, Joachim; Fiedler, Georg Martin
Abstract : Background . Close therapeutic drug monitoring of Cyclosporine (CsA) in transplant outpatients is a favourable procedure to maintain the long-term blood drug levels within their respective narrow therapeutic ranges. Compared to basal levels (C 0 ), CsA peak levels (C 2 ) are more predictive for transplant rejection. However, the application ofC 2 levels is hampered by the precise time of blood sampling and the need of qualified personnel. Therefore, we evaluated a newC 2 self-obtained blood sampling in transplant outpatients using dried capillary and venous blood samples and compared the CsA levels, stability, and clinical practicability of the different procedures. Methods . 55 solid organ transplant recipients were instructed tousesingle-handed sampling of each 50μ L capillary blood and dried blood spots by finger prick using standard finger prick devices. We used standardized EDTA-coated capillary blood collection systems and standardized filter paper WS 903. CsA was determined by LC-MS/MS. The patients and technicians also answered a questionnaire on the procedure and sample quality. Results . TheC 0 andC 2 levels from capillary blood collection systems (C 0 [ng/mL]:114.5 ± 44.5 ;C 2 :578.2 ± 222.2 ) and capillary dried blood (C 0 [ng/mL]:175.4 ± 137.7 ;C 2 :743.1 ± 368.1 ) significantly( P < .01 ) correlated with the drug levels of the venous blood samples (C 0 [ng/mL]:97.8 ± 37.4 ;C 2 :511.2 ± 201.5 ). The correlation atC 0 wasρ cap .-ven . = 0.749, andρ dried blood-ven = 0.432; atC 2 : ρ cap .-ven . = 0.861 andρ dried blood-ven = 0.711. The patients preferred the dried blood sampling because of the more simple and less painful procedure. Additionally, the sample quality of self-obtained dried blood spots for LC-MS/MS analytics was superior to the respective capillary blood samples. Conclusions .C 2 self-obtained dried blood sampling can easily be performed by transplant outpatients and is therefore suitable and cost-effective for close therapeutic drug monitoring.